Gall bladder dysfunction in chronic diabetics (type 2): an ultrasonography based prospective study - Rai, Garjesh S.; Baghel, Vijay Singh; Rai, Tina; Vyas, Mahendra Mohan (International Journal of Research in Medical Sciences, 2016)
Background: Type 2 diabetes mellitus is commonest endocrine disorder now a days and its prevalence is continuously rising in India due to spread of modern life style so its associated complications are also increasing. Gall bladder is one of the commonly affected organs in chronic diabetics, most probably due to autonomic neuropathy which adversely affects gall bladder motility and provokes bile stasis. Methods: This institution based prospective study had been performed among 100 chronic diabetics; randomly selected from diabetic clinic of department of medicine, people’s college of medical science and research centre, Bhopal M.P. India. Only those patients selected for study who have type 2 diabetes mellitus more than 5 yr and have well controlled sugar levels. 100 controls/volunteers were selected for comparative evaluation. All patients and volunteers had undergone abdominal ultrasonography for any existing hepatobiliary pathology and to measure fasting and post fatty meal gall bladder volume. Results: Among 100 chronic diabetics seventy-six (76%) patients didn’t show any hepatobiliary abnormality however cholelithiasis was seen in thirteen (13%) patients, cholecystitis in five (5%) patients and sludge was seen in six (6%) patients. In group of 100 controls ninety-one (91%) didn’t show any hepatobiliary pathology however cholelithiasis was detected incidentally in four (4%) persons, cholecystitis in two (2%) persons and sludge in three (3%) persons. Significant difference is observed in fasting gall bladder volume of chronic diabetics and controls (p value- 0.001). Major difference is also observed in percentage of gall bladder contraction among chronic diabetics and controls (p value- 0.001). Conclusions: Higher fasting gall bladder volume and decreased percentage of contraction both are observed in patients of chronic diabetes mellitus attributed to autonomic neuropathy. Prolonged stasis of bile leads to complications e.g. cholelithiasis, cholecystitis and sludge deposition as late outcome. Hepatobiliary ultrasonography in chronic diabetics can be used as screening tool for early diagnosis of complication and to avoid its serious consequences when presents in emergency and undergone for surgery.